Delirium stories : Hana, Annabel, and Raven - Oliver, Lauren, 1982- (Harper, 2013)
This collection of short stories set in the Delirium world centers around Hana Tate, Lena's mother Annabel and the fierce rebel leader of the Wilds Raven. Each story was published originally as a digital novella. This collection also includes an excerpt from Requiem, the final novel in Oliver's New York Times bestselling series.